The history of the new texts of Zengštokas' Hymnal Giesmes Chriksczionischkos ir Duchaunischkos - Michelini, Guido (Knygotyra, 2006)
The Prussian hymnal Giesmes Chriksczionischkos ir Duchaunischkos, edited by Zengštokas in 1612, continues the tradition of Mažvydas' Giesmes Chriksczoniskas (1566-1570) and Bretkūnas' Giesmes Duchaunas (1589). In addition to several texts reprinted from the previous hymnal, the book contains 51 new hymns, 41 of which are translations from other languages, mostly from German.The paper deals with the history of those new hymns up to 1732, when 27 of them were reprinted: this number remained unchanged in the classical Prussian hymnal.It is pointed out, that the hymnal of 1732 contains only 20% of the hymns which are original texts or translations not connected with German sources: only the most beautiful of them survived and were included in the classical Prussian hymnal.The situation is completely different in the case of the 29 translations from the German: more than 70% of them were reprinted in 1732 and later.This can be explained by the fact that in Prussia a very important role was played by German traditions: most of the Lithuanian translations from the German could not be rejected because they were related to sources which were popular in Prussia. In the light of this it is understandable why half of the rejected translations from the German did not have an equivalent in the Prussian hymnals of the time printed in German.
Keywords: -